УНІФІКАЦІЯ ТА ДИФЕРЕНЦІАЦІЯ ПРОЦЕСУАЛЬНОЇ ФОРМИ: СИНЕРГЕТИЧНИЙ ПІДХІД - Тетерятник, Ганна Костянтинівна (SUPREMANCE OF LAW, 2017)
The article investigates the unification and differentiation of procedural form in the criminal process, using a synergistic approach. Studied properties such criminal procedure system and display them at the unification and differentiation, yak the synergies, the emergence and multiplicative. It determined that differentiation occurs in the system it passes the bifurcation points.
Keywords: unification and differentiation; the synergies; the emergence; the multiplicative; the bifurcation